Design and fabrication of mechanical can crusher / Alif Ikhwan Omar - Omar, Alif Ikhwan (2023)
Manufacturing knowledge was essential for completing this project and ensuring that students understood what they needed to complete. This project involves developing and building a Can Crusher to make it easier for individuals to crush aluminium, tin, and soda cans. This project entails the process of constructing a crusher while taking into account forces and ergonomic factors. After the design was finished, it was turned into a genuine product, with the design serving as a guideline. These projects also include maintaining the security of publishing. In this project, methods and processes like as bending, welding, drilling, and cutting are utilise. This project is primarily focused on developing a new concept for a can crusher that is easier to transport and crush tin. After all of the processes have been completed, this crusher may assist us in better understanding the manufacture and design processes involved in this project.